Legal Standing of Foreign Entities in the Acquisition of Tiktok By Tokopedia: Perspectives from Corporate Law and Competition Law in Indonesia - Putri, Maria Phoebe Tjahja; Lie, Gunardi (Riwayat: Educational Journal of History and Humanities, 2025)
The development of the digital economy has driven new dynamics in the e-commerce sector, including cross-border mergers and acquisitions involving foreign entities. The acquisition of Tokopedia by TikTok is an important case study for understanding the legal implications of vertical integration between global social media platforms and national e-commerce companies. This study aims to analyze TikTok's legal standing as a foreign entity in Tokopedia's ownership structure and examine the application of conditional clearance requirements by the Business Competition Supervisory Commission (KPPU) in maintaining fair competition and protecting national digital economic sovereignty. This study uses a normative juridical method with a legislative, conceptual, and case approach, with primary legal sources in the form of Law No. 40 of 2007, Law No. 5 of 1999, as well as KPPU Regulation No. 3 of 2019 and Permendag No. 31 of 2023. The results of the study show that TikTok formally complies with corporate law provisions, but its ownership structure continues to pose challenges to the principle of separation of foreign entities in the strategic digital sector. Meanwhile, the implementation of conditional clearance by the KPPU serves as a legal instrument to prevent market dominance, cross-platform data abuse, and anti-competitive practices, without hindering economic efficiency. Thus, strengthening supervision and synergy between institutions is key to balancing foreign investment openness with the protection of local businesses and national digital sovereignty